The causal effects of genetically determined immune cells on gynecologic malignancies: a Mendelian randomization study - Li, Yan; Liu, Jingting; Wang, Qiandan; Zhou, Yawei; Zhang, Chunhua; Pei, Jianying (Frontiers in Oncology, 2024)
Evidence from observational studies suggested a connection between immune cells and gynecologic malignancies. To investigate potential causative associations between immunophenotype traits and gynecologic malignancies, we used a two-sample Mendelian randomization analysis.The genetic instrumental variables of 731 immunophenotypes of peripheral blood were obtained by the GWAS database; the GWAS data of common gynecologic cancers were obtained from FinnGen study. The main statistic method was the inversevariance weighted method. We also used the weighted mode, weighted median, and MR Egger for evaluations. The MR Steiger directionality test was further used to ascertain the reverse causal relationship between immune cells and gynecologic cancers.We identified 50 highly probable immunophenotypes and 65 possible ones associated with gynecologic malignancies. The majority of the B cell panel was 3 protective factors in cervical cancer. However, there was a correlation found in the B cells panel with a probable factor associated with an elevated risk of endometrial cancer.Immunophenotypes in the monocyte panel were linked to a lower probability of ovarian cancer and vulvar cancer. All of the gynecologic cancers in our study had no statistically significant impact on immune cells, according to reverse MR analysis.Our study firstly emphasized the genetically predicted causality between immune cells and gynecologic malignancies. This knowledge will be critical to formulating the measures to prevent malignancies in female at risk in future clinical practice.